EXPLORING INTERNAL AND EXTERNAL FACTORS OF SPEAKING ANXIETY IN ACADEMIC PRESENTATIONS AMONG EFL STUDENTS AT JAMBI UNIVERSITY - Dear Atasya Baritanya; Nely Arif; Rd. M. Ali (J-Shelves of Indragiri (JSI), 2025)
Many EFL students face difficulties when delivering academic presentations in English due to feelings of anxiety and a lack of confidence. In fact, presentations are an essential part of the learning process that require strong speaking skills. This problem becomes more complex because English is not their first language, and their limited language proficiency often hinders the fluency and effectiveness of their delivery. This study aims to explore the internal and external factors that contribute to speaking anxiety in academic presentation contexts. A qualitative approach with a case study design was used, involving six eighth-semester students from the English Education Study Program at Jambi University, selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using thematic analysis. The results revealed four internal factors: lack of grammar mastery, Vocabulary Limitations, incorrect pronunciation, and Lack of Self-Confidence. In addition, three external factors were identified: fear of negative evaluation, Lack of Opportunities to Practice Speaking in English, and Speaking Anxiety Triggered by Specific Lecturers. These findings indicate that speaking anxiety is a complex issue that should be addressed through more supportive teaching approaches, including increasing speaking practice and creating a more positive classroom environment.